Use of Palm Olein in Deep-Fried Food Restaurants in Municipal Area of Narathiwat Province Associated with a Risk of Metabolic Syndrome - Promsong, Aornrutai; Luewisawakul, Chusadapak; Bin-u-seng, Nur-eman; Sripradist, Apichaya; Theerakitthanakul, Korkiat (Princess of Naradhiwas University Journal, 2021)
The study was a quasi-experimental research project aimed at examining the oil-consumption characteristics of deep-fried food restaurants in municipal area of Narathiwat Province. The data were collected to analyze acid value (AV), free fatty acid value (FFA) and peroxide value (POV) of the most used oil brands. The survey was conducted using a non-probability sampling of 33 deep fried food restaurants from 13 communities using descriptive and inferential statistics. The result showed that the most popular brands of oil used by deep-fried food restaurants were 303 (30.6%), Cap Athlete (30.6%) and DW7 (10.2%), all three of which were imported palm olein from Malaysia. As heat duration of the study increased, Cap Athlete tended to have a statistically significant increase in AV mean a (p-value = 0.018), while 303 and DW7 tended to have not significant differences in AV (p-value = 0.193 and 0.076, respectively). Also, the AV of each oil brand corresponded to the FFA mean. The POV of all three brands also showed a statistically significant increase with p-value of 0.046, 0.003, and 0.003, respectively. Additionally, analysis for the degradation indicators of heated palm oil showed that AV and POV of the oil used in this study exceeded Codex Alimentarius international food standards. These may contribute to the development of metabolic syndrome among the consumers.